The influence of polysilane chemical structure on optical properties, rubbed film morphology and LC alignment - M. Soroceanu; A. I. Barzic; I. Stoica; L. Sacarescu; V. Harabagiu (eXPRESS Polymer Letters)
Polysilane films were prepared by the drop casting method and their optical and morphological properties have been analyzed in order to investigate their suitability as alignment layers for nematic molecules. The samples do not absorb the radiations in the visible domain, particularly those containing methylhydrosilyl units, and present a transmittance of about 90% starting from 390 to 1100 nm. The optical band-gap is higher than 3.26 eV for all polysilanes indicating a low probability of optical absorption processes in the visible range. The morphology of the pristine samples shows isotropically distributed granular formations. The polymer surface was oriented by rubbing with two types of velvet: one with short fibers and the other with long fibers. The latter generates higher surface anisotropy, as shown by the reduction of the surface texture direction index values. The presence of methylhydrosilyl units allows a denser packing of the polymer structure and thus finer surface periodicities, leading to better orientation of the nematic molecules on the polysilane surface.